PRISM: a Planned Risk Information Seeking Model. - Kahlor L (Health Communication, 2010)
Recent attention on health-related information seeking has focused primarily on information seeking within specific health and health risk contexts. This study attempts to shift some of that focus to individual-level variables that may impact health risk information seeking across contexts. To locate these variables, the researcher posits an integrated model, the Planned Risk Information Seeking Model (PRISM). The model, which treats risk information seeking as a deliberate (planned) behavior, maps variables found in the Theory of Planned Behavior (TPB; Ajzen, 1991) and the Risk Information Seeking and Processing Model (RISP; Griffin, Dunwoody, & Neuwirth, 1999), and posits linkages among those variables. This effort is further informed by Kahlor's (2007) Augmented RISP, the Theory of Motivated Information Management (Afifi & Weiner, 2004), the Comprehensive Model of Information Seeking (Johnson & Meischke, 1993), the Health Information Acquisition Model (Freimuth, Stein, & Kean, 1989), and the Extended Parallel Processing Model (Witte, 1998). The resulting integrated model accounted for 59% of the variance in health risk information-seeking intent and performed better than the TPB or the RISP alone.